Sequencing Chromosomal Abnormalities Reveals Neurodevelopmental Loci that Confer Risk across Diagnostic Boundaries - Talkowski, Michael E.; Rosenfeld, Jill A.; Blumenthal, Ian; Pillalamarri, Vamsee; Chiang, Colby; Heilbut, Adrian; Ernst, Carl; Hanscom, Carrie; Rossin, Elizabeth; Lindgren, Amelia M.; Pereira, Shahrin; Ruderfer, Douglas; et al. (Cell, 2012)
Balanced chromosomal abnormalities (BCAs) represent a relatively untapped reservoir of single-gene disruptions in neurodevelopmental disorders (NDDs). We sequenced BCAs in patients with autism or related NDDs, revealing disruption of 33 loci in four general categories: (1) genes previously associated with abnormal neurodevelopment (e.g., AUTS2, FOXP1, and CDKL5), (2) single-gene contributors to microdeletion syndromes (MBD5, SATB2, EHMT1, and SNURF-SNRPN), (3) novel risk loci (e.g., CHD8, KIRREL3, and ZNF507), and (4) genes associated with later-onset psychiatric disorders (e.g., TCF4, ZNF804A, PDE10A, GRIN2B, and ANK3). We also discovered among neurodevelopmental cases a profoundly increased burden of copy-number variants from these 33 loci and a significant enrichment of polygenic risk alleles from genome-wide association studies of autism and schizophrenia. Our findings suggest a polygenic risk model of autism and reveal that some neurodevelopmental genes are sensitive to perturbation by multiple mutational mechanisms, leading to variable phenotypic outcomes that manifest at different life stages. [Display omitted] ▸ Mechanisms of epigenetic and transcriptional regulation implicated in autism ▸ Balanced chromosomal abnormality breakpoints harbor individual strong-effect genes ▸ Dosage-sensitive loci confer risk to autism from a spectrum of mutational mechanisms ▸ Different alterations in a gene are associated with diverse clinical outcomes Sequencing of balanced chromosomal abnormalities, combined with convergent genomic studies of gene expression, copy-number variation, and genome-wide association, identifies 22 new loci that contribute to autism and related neurodevelopmental disorders. These data support a polygenic risk model for autism and provide new insight into how different types of mutations of the same genes can lead to variable disease phenotypes that manifest at different stages of life.